Evaluasi Sistem Penerangan Lampu Jalan di Perumahan Griya Darma Palembang - Yudi Irwansi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Public Street Lighting (PSL) is one of the essential supporting infrastructures that plays a significant role in ensuring safety, security, and comfort for road users, particularly in residential areas. Inadequate lighting systems may increase the risk of traffic accidents, criminal activities, and reduce public comfort during nighttime. This study aims to evaluate the public street lighting system in Griya Darma Residential Area, Palembang, based on the physical condition of the installation, lighting intensity, uniformity of light distribution, and its compliance with the Indonesian National Standard (SNI 7391:2008) concerning Road Lighting Specifications for Urban Areas. This research employed a quantitative descriptive method with an evaluative approach. Data were collected through field observations, lighting intensity measurements using a lux meter at several observation points, documentation, and interviews with residential management and local residents. The collected data were analyzed descriptively by comparing the measurement results with the applicable standards. The evaluation results indicate that several street lighting points have provided adequate illumination levels; however, some locations still exhibit lighting intensities below the required standard due to lamp performance degradation, relatively wide spacing between lighting poles, and inadequate routine maintenance. Furthermore, the deterioration of several lighting fixtures has affected the uniformity of illumination along the road segments. Based on the findings, this study recommends replacing conventional lamps with more energy-efficient LED lamps, rearranging the spacing of lighting poles according to technical standards, and implementing regular inspection and maintenance programs to maintain the quality of the lighting system. The implementation of these recommendations is expected to improve public safety, security, and comfort while enhancing energy efficiency in the public street lighting system of Griya Darma Residential Area, Palembang.